Long-Term Tolerability and Effectiveness of Once-Daily Mixed Amphetamine Salts (Adderall XR) in Children with ADHD - McGough, James J; Biederman, Joseph; Wigal, Sharon B; Lopez, Frank A; McCracken, James T; Spencer, Thomas; Zhang, Yuxin; Tulloch, Simon J (Journal of the American Academy of Child and Adolescent Psychiatry, 2005)
Objective: To evaluate the long-term tolerability and effectiveness of extended-release mixed amphetamine salts (MAS XR; Adderall XR[R]) in children with attention-deficit/hyperactivity disorder (ADHD). Method: This was a 24-month, multicenter, open-label extension of TWO placebo-controlled studies of MAS XR in children with ADHD aged 6 to 12 years. Subjects (N = 568) began treatment with MAS XR 10 mg once daily, with 10-mg weekly dose increases to optimal effectiveness (maximum dose, 30 mg/d). Effectiveness was assessed with analysis of quarterly Conners Global Index Scale, Parent version (CGIS-P) scores. Tolerability was assessed by monitoring adverse events (AEs), vital signs, physical examinations, and serial laboratory tests. Results: Significant improvements (>30%, p is less than .001) in CGIS-P scores were maintained during long-term treatment. Treatment was well tolerated, and most AEs were mild. The most frequently reported drug-related AEs included anorexia, insomnia, and headache. The incidence of drug-related AEs increased with increasing MAS XR dose, suggesting a dose relationship. Changes in laboratory values and vital signs were modest and not clinically meaningful. Conclusions: In children with ADHD, once-daily 10 mg-30 mg MAS XR was well tolerated and significant behavioral improvements were consistently maintained during 24 months of treatment.